Chemistry of Clinopyroxene from The Deosai Volcanics, Baltistan, N. Pakistan - Hamidullah, Syed (Journal of Himalayan Earth Sciences, 1991)
Seventy analyses of clinopyroxene phenocrysts from the Deosai volcanics were obtained and tested for substitutions and other petrogenetic characters. The data show an overall core-margin substitution of xCa+xNa+xFe3+ +xtAl+xTi =xSi +xMg+xFe2 + +xMn type in the phenocrysts, with representing the actual amount of a cation entered or replaced, and which can be determined precisely from its variation along with unit variation of Si. The data also indicate crystallization in a temperature range of 1100-1200 oC, under highly variable pressure, from a basaltic magma of alkaline (but transitional to non-alkaline) characters.